PIK3CA c.3140A>G mutation in a patient with suspected Proteus Syndrome: a case report. Issue 7 (2nd June 2018) - Valentini, Virginia; Zelli, Veronica; Rizzolo, Piera; Silvestri, Valentina; Alimandi, Maurizio; D'Aloia, Maria Michela; Giustini, Sandra; Calvieri, Stefano; Richetta, Antonio Giovanni; Monteleone, Giovanni; Ottini, Laura
Key Clinical Message: We present a patient with suspected Proteus Syndrome, an overgrowth disorder associated with AKT1c.49G>A mutation. NGS analysis detected PIK3CAc.3140A>G mutation in the patient's affected tissue allowing for PROS (PIK3CA‐related overgrowth spectrum) diagnosis. The overlapping clinical features in overgrowth disorders highlight the importance of molecular testing for a correct diagnosis. Abstract : We present a patient with suspected Proteus Syndrome, an overgrowth disorder associated with AKT1c.49G>A mutation. NGS analysis detected PIK3CAc.3140A>G mutation in the patient's affected tissue allowing for PROS (PIK3CA‐related overgrowth spectrum) diagnosis. The overlapping clinical features in overgrowth disorders highlight the importance of molecular testing for a correct diagnosis.